(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Previous studies demonstrate the feasibility of using wave-powered water pumps to upwell cold, nutrient-rich ocean water to the surface for enhancing macroalgal (i.e. kelp) aquaculture. The UNH-AMEC wave-powered water pump (wave pump) is a two-body point absorber wave energy converter, which is comprised of a wave follower buoy and a spar buoy. A numerical model and ocean test of the wave pump yielded good agreement between results (Kimball et al. 2025), providing sufficient confidence in the model for its continued use in further device development. The model, test results, and the experience gained from the ocean test were then used to iterate and analyze an improved design. Three areas of improvement are investigated, including increasing the volumetric flow rate of the pump, upgrading the device’s survivability in waves, and simplifying the manufacturing and deployment process. The main change in design for the improved device includes a larger diameter piston, which requires a larger diameter float and heave plate. The device is numerically modeled using WEC-Sim to obtain the volumetric flow rate of the proposed improved design. In a JONSWAP wave spectrum with significant wave height of 0.70 m and period of 6.0 seconds, the average volumetric flow rate was modeled at 32 m3 hr-1. This is an increase in volumetric flow rate of approximately eight times compared to the ocean test of the original device design in similar wave conditions. The flow rate for the improved design is then compared to other previously tested wave pump designs. The ocean tested wave pump exhibited difficulty self-righting for large tip (pitch) angles. Therefore, hydrostatic stability and self-righting capabilities for the improved wave pump are analyzed to increase survivability of the device. The device was numerically modeled in tip angle increments of 10° and found to be both hydrostatically stable and have a positive righting moment for tip angles up to 90° from the vertical axis. In part, this design improvement was due to the larger heave plate, which acts as a sea-anchor, at the bottom of the device’s spar. The wave pump design that includes the improved volumetric flow rate and survivability advances the practicality of wave pumps for use in aquaculture systems. Future work with the improved design could include further validation of the model results with a scaled wave tank model test (1/3 scale) and an ocean test of a full-scale device. Another area for future investigation could include quantifying the additional kelp grown due to colder, nutrient-rich available waters upwelled from a wave-powered water pump.